1997
DOI: 10.1016/s1097-2765(00)80012-x
|View full text |Cite
|
Sign up to set email alerts
|

FMRP Associates with Polyribosomes as an mRNP, and the I304N Mutation of Severe Fragile X Syndrome Abolishes This Association

Abstract: Fragile X mental retardation is caused by the lack of FMRP, a selective RNA-binding protein associated with ribosomes. A missense mutation, I304N, has been found to result in an unusually severe phenotype. We show here that normal FMRP associates with elongating polyribosomes via large mRNP particles. Despite normal expression and cytoplasmic mRNA association, the I304N FMRP is incorporated into abnormal mRNP particles that are not associated with polyribosomes. These data indicate that association of FMRP wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
431
2
3

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 471 publications
(460 citation statements)
references
References 44 publications
24
431
2
3
Order By: Relevance
“…FMRP is associated with actively translating polyribosomes in an RNA-dependent manner via messenger ribonucleoprotein (mRNP) particles [7]. A missense mutation in the second KH domain of FMRP (I304N), which results in severe mental retardation, prevents this polyribosome association, suggesting that the association of FMRP with polyribosomes is functionally important [7].…”
Section: Glossarymentioning
confidence: 99%
See 1 more Smart Citation
“…FMRP is associated with actively translating polyribosomes in an RNA-dependent manner via messenger ribonucleoprotein (mRNP) particles [7]. A missense mutation in the second KH domain of FMRP (I304N), which results in severe mental retardation, prevents this polyribosome association, suggesting that the association of FMRP with polyribosomes is functionally important [7].…”
Section: Glossarymentioning
confidence: 99%
“…60% amino acid identity and contain two types of RNA-binding motifs: two ribonucleoprotein K homology domains (KH domains) and a cluster of arginine and glycine residues (RGG box). Owing to their similarities, it has been postulated that FXR1P and FXR2P can partially compensate for the loss of FMRP, although expression levels of both FXR1P and FXR2P are not altered in the cells from fragile X patients or the Fmr1-knockout mice [7]. The fragile X-related gene family has been well conserved during evolution.…”
mentioning
confidence: 99%
“…A hypothesis explaining the probable function of FMR1 is that it might be involved in binding RNA transcripts within the nucleus and transporting them across the nuclear membrane for translation in the cytoplasm. In the Case of the point mutation in addition to its inability to bind effectively to the transcripts generated, the mutant FMRP forms abnormally small mRNP particles which fail to be transported across the nucleus and therefore are not selected for translation (30). The fact that FMR1 is expressed in actively dividing cells, cosediments with 60s ribosomes and strongly interacts with Rab40, a protein found in the nuclear pores seem to support its postulated function (31).…”
Section: Fragile X Mental Retardation Protein (Fmrp)mentioning
confidence: 99%
“…These mRNP are associated with the translating ribosomes (polyribosomes) as demonstrated by the use of translation initiation inhibitors (Corbin et al, 1997;Feng et al, 1997). Still, the question of a functional interaction between FMRP and the ribosome seems unsolved.…”
Section: The Fmrp Mrnp Particle(s)mentioning
confidence: 99%
“…After an initial conclusion that FMRP was intimately associated with the ribosome, further studies suggested that FMRP does not interact directly with the ribosomes themselves but rather through the interaction with mRNA. Indeed, ribosomes can be depleted from mRNPs by EDTA treatment, while FMRP remains associated to a complex of large size, with a sedimentation peak centered at 100S, clearly distinct from heaviest 60S ribosomal subunits (Feng et al, 1997;Ohashi et al, 2002). However, the recent report of the isolation of ribosomal proteins directly associated with the Drosophila FMRP homolog suggests that a direct interaction between FMRP and the ribosome is likely to occur at some point .…”
Section: The Fmrp Mrnp Particle(s)mentioning
confidence: 99%